Organizational citizenship behavior: peran komunikasi interpersonal, semangat kerja, dan kepuasan kerja pada pegawai PT Aromatik Yogyakarta - Rositasari, Intan; Soni Kurniawan, Ignatius (Jurnal Paradigma Ekonomika, 2022)
The purpose of this finding is to examine the effect of interpersonal communication, work morale on Organizational Citizenship Behavior (OCB) with job satisfaction as a mediating variable at PT Aromatik Yogyakarta. The population in this study is PT Aromatik Yogyakarta with 60 employees as respondents. The sampling method used a saturated sample or all employees became respondents. The method used is quantitative. The data analysis technique used multiple linear regression and Sobel test. The results showed that interpersonal communication on job satisfaction and interpersonal communication on OCB did not have a significant effect. Work spirit on job satisfaction and work spirit on OCB have a significant positive effect. Job satisfaction on OCB has no effect. Does not mediate job satisfaction on interpersonal communication variables, work spirit on OCB. Â